Analisis Stakeholder dalam Program CSR-BUMN: Balkondes (Balai Ekonomi Desa) Kecamatan Borobudur, Kabupaten Magelang - Priska Grace Filia; Laila Khalid Alfirdaus (Journal of Politic and Government Studies, 2020)
Community development is no longer just the responsibility of the government. A third party, namely the company, is also responsible for the development and improvement of people's welfare. The Ministry of BUMN participated in improving the community's economy by sparking the development of the Balkondes (Village Economic Center) in Borobudur, Magelang. Certainly not alone, but inviting 20 SOEs as sponsors and forming a Co-BUMN that works directly to accelerate the success of the program, together with the community that is the program's target.Qualitative research method use in this research. Primary data sources were obtained through interviewees. While secondary data comes from documents, articles, and other sources related to research. While the analysis technique used in this study is a qualitative analysis to analyze data in the form of description, drawing, and drawing conclusions from the object under study. The object of research is the community as the manager of Balkondes, the Village Government, and the relevant SOEs. The results showed that the relations between actors formed were inseparable from the ups and downs of collaborative and conflictual relations. There have always been pros and cons that have arisen since the inception of the Balkondes program. However, there is a desire of the community to improve the economic level and the persistence of PT. Manajemen CBT Nusantara as a Co-BUMN is able to reduce small conflicts that have arisen. The emergence ofself-sufficient rural communities is a long-term shared goal of the Balkondes program.Keywords: Stakeholder Analysis, Relations Between Actors, Community Empowerment.